An Insulin-Like Growth Factor in Rhodnius prolixus Is Involved in Post-feeding Nutrient Balance and Growth - Defferrari, Marina S.; Orchard, Ian; Lange, Angela B. (Frontiers in Neuroscience, 2016)
Growth of organisms is modulated by the availability of nutrients and energy, and is mostly regulated by insulin-like growth factors (IGFs) through the insulin signaling system. In insects, IGFs produced by the fat body induce cell division during the molt cycle, regulate adult body size and have metabolic effects. Here we describe an IGF from the hematophagous hemipteran Rhodnius prolixus and show its activity in regulating growth and metabolism in the post-feeding period during the fifth, and last, nymphal instar. Rhopr-IGF transcript is present in a variety of tissues, with greatest expression in the fat body, the dorsal vessel and the CNS. We silenced the expression of the transcript using RNA interference, and at two weeks after feeding, insects with reduced Rhopr-IGF expression showed increased hemolymph lipid and carbohydrate levels when compared to controls, but no differences were observed in fat body lipid or carbohydrate content. In order to assess the role of Rhopr-IGF in post-feeding growth, double stranded IGF-injected insects were followed through ecdysis, and this treatment resulted in shorter adults, with shorter and narrower wings, when compared to controls. The results suggest that Rhopr-IGF modulates growth in R. prolixus most likely through altering the usage of nutrients that are available in the hemolymph.